Diagnosis of vaginitis: time to improve and move on - Baptista, Pedro Vieira; Eleutério Jr, José (Brazilian Journal of Sexually Transmitted Diseases, 2020)
Vulvovaginitis is the ultimate example of Potter Stewart’s “I know it when I see it”: everybody knows what it is, but no one can find an adequate and encompassing definition. Despite this obvious limitation, one thing is factual: vulvovaginitis is the reason for at least 2% of office appointments among women, representing a huge amount of time and money spent(1). The human suffering (physical and psychological) associated is uncountable and comes in different dimensions: the recurrence of symptoms, severe conditions misdiagnosed or undiagnosed (even malignant and premalignant ones), and increased risk of developing gynecological and obstetrical complications. The list of complications is extensive, including: pelvic inflammatory disease, ectopic pregnancy, infertility, sexually transmitted infections (HIV, HPV, herpes), [...]